Pijakan Epistomelogi Dakwah - Syukriadi Sambas (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
Philosophical base for any science is a sine quo none, including ilmu dakwah. It is hence an indispensable necessaty for ilmu dakwah and all experts on it are required to have a good mastery on it, without which they would not be capable enough to develope ilmu dakwah. Tbis paper aims at providing some necessary materials as an attempt to enlift ilmu dakwah and to empower its scientists.In doing so, this paper will first take the advantage of Alquran as the inspirational source of the philosophy of dakwah. It is here held that Alquran provides huge sources for ilmu dakwah to be more developed and established.Secondly, it attempts to makes clear the definition and goals of the philosophy of dakwah. Tbis is to draw distinctive features of academic bases of the philosophy of dakwah. Then, it uncovers the need of hwnan beings to the activities of dakwah. Here the writer insists the inseparability of mankind from the movement of dakwah in support of their life. Finally, it explores the basic principles and epistemology of the philosophy of dakwah, as a way of providing a sort of guidelines for any effort of developing lmu dakwah.